Numerical modelling of a large tunnel lining in a creeping rock mass based on 20 years monitoring data. Issue 1 (August 2021) - Plassart, R; Martin, F; Saïtta, A; Lopard, G
Abstract: The French project of deep geological storage for nuclear waste (Cigéo) gives rise to a lot of innovative issues for underground space technologies. For example, the nuclear activity of the waste generates temperature effects on the lining, needing to mitigate the number of waste containers in the gallery section. For the Intermediate-Level waste (ILW), thanks to lower temperature effects, the number of containers in the cross section can safely be increased. Therefore, a largest diameter gallery (10 meters) could be more cost effective. The challenge is to design the lining of such a gallery for 100 years in a context of high displacements, due to 500 meters overburden and the creeping behaviour of the rock mass (COx argillite). To improve our understanding of long term behaviour of large galleries, this paper details the experience of the road tunnel of Chamoise (France), including an advanced processing of the available data (rock and lining displacements, linings yielding) recorded since the tunnel excavation, more than 20 years ago. Besides, a numerical modelling of the tunnel has been carried out, using two constitutive laws accounting for a viscoplastic mechanism: L&K (EDF) and H&B-Lemaitre (ANDRA). The simulations results have then been compared with the processed records on 20 years. Finally, the calculations have been carried on until 100 years, improving the demonstration of feasibility of a large gallery in claystone for the challenging Cigéo project.